(De)humanizing Metaphors of People in Pain and Their Association with the Perceived Quality of nurse-patient Relationship. (2nd October 2022) - Diniz, Eva; Castro, Paula; Bernardes, Sónia F.
ABSTRACT: Metaphors are central in communication and sense-making processes in health-related contexts. Yet how the metaphors used by health-care-professionals to make sense of their patients and their relations to them are associated to the perceived valence of their clinical encounters is underexplored. Drawing-upon the ABC Model of Dehumanization, this study investigated how the humanizing or dehumanizing metaphors nurses' use for making sense of their pain patients are associated with how they perceived their relationships with them. Fifty female nurses undertook individual narrative-episodic interviews about easy/difficult cases in pain care. A content analysis classified the metaphors, identifying eight classes reflecting different types of patients (de)humanization. A multiple correspondence analysis extracted patterns of metaphors and their association with the perceived characteristics of the patient-nurse relationship. It showed how these patterns were not associated with patient sex or socioeconomic status (SES) but were related to the perceived valence of the clinical relationship. By uncovering how patient metaphors guide nurses' sense-making and potentially modulate interactions in clinical encounters, these findings may contribute to improve quality of pain care.